Risk Assessment during Covid-19 and Learning from Home: Evidence from University Students in Indonesia - Herman Rahadian Soetisna; Ari Widyanti; Airin Syafira; Dwita Astari Pujiartati (Jurnal Optimasi Sistem Industri, 2021)
COVID-19 pandemic has become an international concern. Policies to prevent the spread of disease, such as learning from home, are applied to university students. The present study examines the risk assessment in relation to physical, mental, and psychosocial condition of Indonesian students toward COVID-19 and learning from home. This study involves 838 Indonesian students. A questionnaire consisting of demographic data and constructs from a comprehensive literature study regarding COVID-19 related issues and learning from home issues was developed. Most Indonesian student respondents have a good knowledge of COVID-19 and have received accurate information from the government. The anxiety level during COVID-19 is mild. In relation to physical condition, most students reported musculoskeletal symptoms in the neck, shoulder, and back areas. The respondents conduct preventive behavior against COVID-19 spread, with lack of physical exercise. In relation to mental and psychosocial condition. In relation to mental and psychosocial condition, respondents report moderate mental workload and proper social support from lecturers and friends. In conclusion, most Indonesian university students have a good knowledge and proper attitudes toward COVID-19 and learning from home, which are important in combating and passing through the pandemic.